Corporate Governance and Directors Duty to Act in Good Faith and in the Best Interest of the Company: The Malaysian Experience - Masum, Ahmad; Nizam Salahudin, Shahrul; Hanan Haji Abdul Aziz, Hajah (International Journal of Engineering and Technology, 2018)
Corporate governance is not a legal term. It is a term that refers broadly to the rules, processes, or laws by which businesses are operated, regulated, and controlled. It has traditionally specified the rules of business decision making that apply to the internal mechanisms of companies. Corporate governance mechanisms have the purpose of monitoring and controlling the management of corporations resulting in more effective management and to enhance shareholder value. The aim of this paper is to examine the duty of company directors to act in good faith and in the best interest of the company by way of making reference to the Malaysian experience. This paper adopts a legal library based research methodology focusing mainly on primary and secondary legal sources. The paper concludes that although directors must exercise their discretion in good faith, the fiduciary duty to act in good faith in the interests of the company is a subjective duty. There is no breach where the directors act in what they honestly believe to be in the interests of the company. The courts are generally reluctant to override the business judgment of directors. The paper recommends that courts should adopt a flexible approach in dealing with directorsâ€™ duty to act in good faith and in the best interest of the company. The erosion of a directorâ€™s obligation to act in good faith does not bode well for the modern corporation and the economy, and a meaningful interpretation of â€œnot in good faithâ€ is necessary to help halt the erosion.Â Â Â Â Â